Creating Business Opportunities for The Pantai Labu Pekan Village Community and An Increase in Hb In Breastfeeding Mothers by Consumerizing Apple Juice Mixed With Beets - Ningtias, Anggitha; Dalimawaty Kadir; Muhammad Iqbal Ilhamsyah; Mhd Alvin Ginting; Ananda Putri Mawaddah; Ayu Wulandari; Devi Pratiwi; Kiki Amalia Harahap (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Iron deficiency anemia is a common health issue among breastfeeding mothers, which can affect the quality of breast milk and the mother's health. This study evaluates the effectiveness of apple juice mixed with beet consumption in increasing hemoglobin (HB) levels in breastfeeding mothers and the potential of this juice as a business opportunity. The research method involved an experimental study with treatment and control groups. The results showed a significant increase in HB levels in the group consuming apple juice mixed with beets. Additionally, the market potential for this product indicates a promising business opportunity for the community. This study suggests the implementation of apple juice mixed with beets as a nutritional intervention and a local business opportunity.